Boosting persuasion: The attention benefits of multiple narrating voices - CHANG, Hannah H. (Institutional Knowledge at Singapore Management University, 2023)
The "Voice Numerosity Effect”: When hearing different voices narrating a marketing video facilitates persuasion. In a forthcoming paper in the Journal of Marketing Research, we investigate the role of voice (narrator) numerosity in marketing videos (Chang, Mukherjee, and Chattopadhyay 2022). For example, consider the following two real-life examples: a product video introducing Apple’s AirPods Max had two narrating voices while a product video introducing Apple’s new Macbook Pro had a single narrating voice. Does the difference in the number of narrating voices influence consumers’ attention and subsequent behaviour?